Morphometric evaluation of caprine spermatozoa by HT-IVOS System at pre-freeze and post-thaw stages of cryopreservation - SUNDARARAMAN, M N; EDWIN, M JOHN (The Indian Journal of Animal Reproduction, 2023)
Semen samples were collected from two adult Boer Grade (Boer x Local) goats by artificial vagina method, evaluated, extended in Tris-Egg yolk-Glycerol based diluent and frozen by French straw technique. After dilution, a portion of extended semen was further diluted to prepare thin sperm smears. The smears were stained with Stat III, Andrology stain for morphometric evaluation by HT-IVOS system. The frozen samples were thawed and samples showing acceptable sperm motility were further diluted for preparation of semen smears for staining and evaluation by HT-IVOS system (CASA). A total of 1000 spermatozoa each at pre-freeze and post-thaw stages of cryopreservation, involving 6 different samples each from two bucks were analysed for morphometric traits viz., major axis, minor axis, elongation, head area, perimeter and tail length. Highly significant (P 0.01) differences were noticed for most of the morphometric traits except for minor axis of the sperm head and tail length between different stages of semen processing for cryopreservation. The variations obtained in major axis, minor axis, elongation, head area and perimeter of the sperm head between bucks were also highly significant (P 0.01 ). Most of the morphometric traits of the sperm heads of frozen-thawed spermatozoa also exhibited highly significant (P 0.01) variation between bucks. Cryopreservation resulted in irreversible changes in structural integrity of caprine spermatozoa.